Keeping quilt (The) - Polacco, Patricia (Aladdin Paperbacks, 1988)
A homemade quilt ties together the lives of four generation of an immigrant Jewish family, remaining a symbol of their enduring love and faith.
TR/PS
Keywords: Quilts -- Fiction; Jews -- Fiction; Immigration and immigration -- Fiction